Between Dao and history: two Chinese historians in search of a modern identity for China - Schneider, Axel (History and theory, 1996)
Since the beginning of the twentieth century Chinese historians have struggled to reform Chinese historiography and to establish a new identity for the Chinese nation. In this article I analyze the historiography of Chen Yinke and Fu Sinian as a case study for this ongoing process of reform. Although both were bound into the dichotomy of dao and history as established by Benjamin Schwartz, they represent quite different solutions to the question of how the relationship between norm and fact has to be conceptualized. Chen Yinke's historiography is one of the first examples of the emerging pluralization of the relationship between dao and history, since he is aware of the subjective influences that affect a historian's research and seems to recognize that these influences can be positive. Fu Sinian's historiography on the other hand is an example of the reintegration of dao and history. He explicitly refutes the claims of theory and interpretation, but actually reintroduces theoretical explanations without identifying them as such. Thus his methodology can be described as a hidden reintegration of dao and history, of norm and fact. These different methodological views imply two divergent approaches to the nature of Sino-Western cultural relations, and to the role of the historian in modern Chinese society. Chen recognizes the fundamental differences between China and the West and assumes the equality of the unequal, that is, the principle that there are no absolute values that could function as norms for comparing different cultures. Because of the pluralization of the relationship between dao and history, the historian is no longer in a position to guide society ideologically and philosophically. He is freed from the constraints of political engagement and assumes the role of a kind of cultural guardian. By contrast Fu assumes a single world civilization based on a universal methodology for accumulating knowledge. He is unable to establish continuity between the particular Chinese past and its present and therefore cannot establish an identity that is both new and at the same time Chinese. Fu also takes a position different from Chen on the role of the historian. He postulates a complete separation from politics, but in historiographical as well as in political practice, he adopts the role of ideological leader and moral critic of those in power.